Maximizing the Contribution of Mining industry to Sustainable Development: Case Study at PT FREEPORT INDONESIA - Mulyana, Fajar; Djajadiningrat, Surna Tjahja (The Indonesian Journal of Business Administration, 2013)
Historically, mining has had a bad reputation of being destructive to the environment and social-cultural. Issues such as the depletion of resources, loss of biodiversity, lack of contribution to the local area's development, human rights violation, and the negative impacts on local communities are central to the mining industry’s operations. Despite mining industry claims that comprehensive environmental and corporate social responsibility programs have been fully implemented, the mining industry is still under high pressure to improve its economic, social and environmental performance. PT Freeport Indonesia (PTFI) one of the country's biggest recipients of foreign direct investment is located in the remote area in Papua and interacts with indigenous people. Despite PTFI is one of the largest taxpayers in Indonesia, and contributor of over US$60 billion to the country's national gross domestic product since 1992, the company is still demanded by stakeholder to contribute more to the local, regional, and national development. The objective of this final project is to analysis the source of the most problem and to define the proper solutions to resolve the problems faced by the mining company especially PTFI in order to be sustainable and to be part of sustainable development. The methodology used in this research project consists of assessment of current business situation started with external and internal environmental scanning, PESTEL analysis is used to study external factors, and then is combined with the SWOT situation analysis. Keyword: Sustainable Development, Mineral Mining, Root Cause Analysis, PESTEL, SWOT Analysis